Associations of cartilage intermediate layer protein 1 and hypoxia-inducible factor-1-alpha with transthoracic echocardiography results in patients with heart failure with preserved ejection fraction - Yu. S. Timofeev; Ju. A. Fokina; V. A. Metelskaya; A. R. Afaunova; E. G. Chernyshenko; A. A. Ivanova; O. N. Dzhioeva; O. M. Drapkina (Российский кардиологический журнал, 2024)
Aim. To evaluate the relationship of serum concentrations of myocardial remodeling and cellular hypoxia biomarkers cartilage intermediate layer protein 1 (CILP-1) and hypoxia-inducible factor-1-alpha (HIF-1α) with paraclinical parameters in patients with heart failure with preserved ejection fraction (HFpEF) and in the control group.Material and methods. The study included 47 patients diagnosed with HFpEF, aged from 47 to 79 years, who were treated from May 2018 to December 2019 in the hospital of the National Medical Research Center for Therapy and Preventive Medicine. The control group consisted of 32 people without a diagnosis of HFpEF, matched by sex and age. All participants underwent transthoracic echocardiography with assessment of diastolic function. Serum concentrations of CILP-1 and HIF-1α were determined by enzyme immunoassay using standardized test systems (RayBio and Clone-Cloud, USA).Results. In patients with HFpEF, the median serum concentrations of CILP-1 (3,24 ng/ml) and HIF-1α (14,3 pg/ml) were not significantly different from the values obtained in the control group (3,6 ng/ml and 7,5 pg/ml, respectively). Significant correlations of CILP-1 with echocardiographic indicators of the left ventricular interstitial fibrosis severity were revealed, while echocardiographic markers of HFpEF positively correlated with the HIF-1α level.Conclusion. Although the serum concentrations of CILP-1 and HIF-1α do not differ depending on HFpEF presence, it demonstrates an association with a number of echocardiographic parameters both in subgroups of patients with HFpEF and in subgroups of controls with different body mass index.